The Role of Social Media and Community in Purchasing Decisions Via Customer Equity - Gregorios Delbert; Muhammad Khevin Martinier Wisudyanto; Sarah Azalia Putri Harla; Asnan Furinto (Journal of Business, Social and Technology, 2026)
Background: The rapid growth of digital communication platforms has significantly reshaped how premium sports brands interact with consumers. In emerging lifestyle sports such as padel, purchasing decisions are no longer influenced solely by product specifications or brand reputation but also by digital engagement and community participation. Objective: This study examines how Social Media Marketing (SMM) and Community Engagement (COM) affect Purchasing Decisions (PD) through the mediating role of Customer Equity dimensions: Value Equity, Brand Equity, and Relationship Equity. Methods: A quantitative survey was conducted among 123 consumers of premium padel equipment across major Indonesian cities. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The results indicate that although SMM and community participation significantly enhance all dimensions of customer equity, they do not directly influence purchasing decisions. This finding is attributable to the high-involvement nature of premium padel equipment, which requires extensive cognitive evaluation and physical trials before purchase. Instead, purchasing behavior is driven primarily by Value Equity and Relationship Equity. Relationship Equity emerges as the most influential determinant. Brand Equity, contrary to conventional branding assumptions, does not significantly predict purchasing decisions in this context. Conclusion: These findings suggest that, in performance-driven sports markets, consumers prioritize perceived functional value and relational trust over symbolic brand prestige. The study extends Customer Equity Theory to the niche padel equipment market and provides practical implications for brands seeking to convert digital engagement into tangible sales outcomes.